REVOLUTION AND STATUS OF WOMEN: GENDER AND POLITICAL ASPECTS - Kobets, Y. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2018)
The twentieth century will be remembered as a time of the revolutions that had a consequence a radical transformation of social relations. There was also a so-called "Quiet revolution" or "revolution of women", which led to a significant number of their emancipation. The article deals with the change of gender stereotypes under the influence of revolutionary changes during the year ot 1917, the period of formation the establishment of independence, during the events of the Maidan and the Revolution of Virtue. The research document contains a political analysis of socio-political processes of participation and role of women that took place in Ukraine and in the world. The author emphasizes the features of the displaying problems depending on a particular ideological and political situation, political regime. It became possible with the help of a systematic and integrated approach to consideration of the problem to supplement the general picture of revolutionary events, to reveal the female component of these periods in all of it's diverse manifestations, to make a certain contribution to the field of gender research in political science. The focus is on the struggle for women to equalize rights with men in the economic, political, cultural spheres of life, as well on their participation in general political processes.